Square root of a multivector in 3D Clifford algebras - Dargys, Adolfas; Acus, Artūras (Nonlinear Analysis: Modelling and Control, 2020)
The problem of square root of multivector (MV) in real 3D (n = 3) Clifford algebras Cl3;0, Cl2;1, Cl1;2 and Cl0;3 is considered. It is shown that the square root of general 3D MV can be extracted in radicals. Also, the article presents basis-free roots of MV grades such as scalars, vectors, bivectors, pseudoscalars and their combinations, which may be useful in applied Clifford algebras. It is shown that in mentioned Clifford algebras, there appear isolated square roots and continuum of roots on hypersurfaces (infinitely many roots). Possible numerical methods to extract square root from the MV are discussed too. As an illustration, the Riccati equation formulated in terms of Clifford algebra is solved.
Keywords: geometric Clifford algebra; experimental mathematics; square root of multivector; infinitely many roots; Riccati equation